1996
DOI: 10.1093/treephys/16.11-12.899
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal branch and fine root growth of juvenile loblolly pine five growing seasons after fertilization

Abstract: In 1989, we established two replications of two fertilization treatments in a 10-year-old loblolly pine (Pinus taeda L.) plantation. Between March and September 1993, branch internode and needle fascicle expansion in the upper and lower third of crowns were measured weekly on three south-facing branches of each of four trees, and new root initiation and elongation were measured at 10-day intervals in three vertical rhizotrons per plot. In one replication, soil water content was measured daily. Fertilization si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Removal of the whorl and lateral buds and whorl branches had a more severe effect on plant growth and caused a reduction in root length and DW. Removal of a significant part of the photosynthetic area was the likely reason for the reduction in root and shoot growth, which was in accordance with [26], who observed that current photosynthesis was responsible for new root growth in conifer species, and with [24], who found similar results in Pinus taeda L.…”
Section: Discussionsupporting
confidence: 87%
“…Removal of the whorl and lateral buds and whorl branches had a more severe effect on plant growth and caused a reduction in root length and DW. Removal of a significant part of the photosynthetic area was the likely reason for the reduction in root and shoot growth, which was in accordance with [26], who observed that current photosynthesis was responsible for new root growth in conifer species, and with [24], who found similar results in Pinus taeda L.…”
Section: Discussionsupporting
confidence: 87%
“…Sword et al (1996) found that on Gulf Coastal Plain sites, new fascicle needles of loblolly Fig. 2 Seasonal predawn and daytime xylem pressure potential (Y pd and Y d ) and soil volumetric moisture content (SMC) in a 16-year-old loblolly pine plantation.…”
Section: Discussionmentioning
confidence: 99%
“…The highest P n was observed in the spring, when ambient conditions were most favorable. The photosynthate exported from 1-year-old foliage during that period may have been one of the major carbon sources for flush shoot elongation and needle growth (Dickson 1989;Sword et al 1996). During the early growing season, therefore, tree carbon balance could be significantly affected by nonoptimal environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…While rhizotrons also provide data on root length (e.g. : Field studies: Itoh 1985;Sword et al 1996;West et al 2003;Davis et al 2004. Reviews: Vogt et al 1998Hendricks et al 2006), the unit of measurement (root length per unit area of observation screen) is not easily integrated into models of plant water and nutrient uptake.…”
Section: Root Characteristicsmentioning
confidence: 99%